IMPLEMENTASI PERATURAN DAERAH KOTA SAMARINDA NOMOR 13 TAHUN 2011 TENTANG RETRIBUSI JASA UMUM - Desy Piyonita (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT National Development is improving the quality of human effort and the people of Indonesia are conducted on an ongoing basis, based on national capabilities, by utilizing advanced science and technology and should be able to pay attention to the challenges of global development. Implementation refers to the national identity and values aimed at realizing the lofty universal life sovereign nation, equitable, prosperous, advanced, independent, and firm moral and ethical strength. Thus, building the welfare of the people and cultures endurance is an important agenda and strategic development.Retribution as well as local tax is one of the original income is expected to be one of the sources of financing of local governance and development, to improve and equalize the welfare of the community. Opinions Ahmad Yani "Regional provincial, district / city given the opportunity to explore the potential of financial resources by specifying the type of charges other than those specified, that they meet the established criteria and in accordance with the aspirations of the people".Public services are services provided or administered by local governments for the purpose of the benefit and the benefit of the general public . Form of public services provided or administered by the Regional Government to the general public realized in services . Thus , Public service levies are levied against the individual or entity who uses / enjoys public services are provided or administered by the Government . When compared to the application of the appropriate Regional Regulation No. 13 of 2011 with the objec field , many of the policies carried out by the parties in the running application retibusi Dispenda this , the statement by the Public Relations Staff Dewi Wahyuni Revenue Office " most people do not understand this retribution for what , and communities to distrust us , they must have felt the proceeds of the levy will be perverted , but for our institution never did misappropriation of funds , there may be some who do that and that person , so we never give sanction to the public or company who have or are late in paying a levy , we do a lot of public policies that actually spoil , but we did this for the good of the city so that all of the actors or public service users to pay levies , although late , as long as they pay . "Under real conditions Revenue Samarinda, the authors hope Dispenda more firmly against the policies of retribution and the sanctions provided so that people pay more attention to the payment of the levy in accordance with applicable regulations.